Does M&A financing affect firm performance under different ownership types? - Chen, J.; Zhao, X.; Niu, X.; Fan, Ying Han; Taylor, Grantley (2020)
Mergers and acquisitions (M&A) are an essential way for enterprises to achieve sustainable development. As large sums of money are typically involved in M&A transactions, financing is a vital factor in outcomes. This study examines the relation between equity and debt financing of M&A on subsequent performance, and the effect of ownership (state-owned enterprises versus private-owned enterprises) on M&A performance in China. We are motivated to examine the relation between financing methods and M&A performance in China because the differences in ownership, resource availability and policy support by the government for many firms may affect subsequent performance. Using a large sample of Chinese A-share listed companies between 2009 and 2016, we find that equity-financed M&A transactions lead to significantly better performance than debt-financed transactions. Equity-financed M&A transactions of state-owned enterprises (SOEs) perform significantly better as compared to debt-financed M&A, whereas equity-financed M&A transactions of private-owned enterprises (POEs) have little effect on their performance. This study extends our insights into the relation between M&A financing types and firm performance under different ownership types in the context of emerging markets.